Rise and “decline” of Chinese Wolf Warrior Digital Diplomacy - Benedicto Solsona, Miguel Ángel (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2024)
Chinese officials use social media to project their discourse abroad. The use of wolf warrior diplomacy promotes a positive image of China's achievements and criticizes the West through disinformation techniques and through social media. Chinese assertiveness is increasing in foreign policy and coordinated from the leadership of the Communist Party on issues of national interest such as Xinjiang, Taiwan and Hong Kong or in defense of policies to control the COVID-19 pandemic. However, the toughness of digital diplomacy could decline if Beijing wants to maintain relations with the West in a period of adjustment like the one it is experiencing.